2012
DOI: 10.1093/toxsci/kfs224
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Protein Biomarker Panel for Assessment of Neurotoxicity Induced by Kainic Acid in Rats

Abstract: Glutamate excitotoxicity plays a key role in the etiology of a variety of neurological, psychiatric, and neurodegenerative disorders. The goal of this study was to investigate spatiotemporal distribution in the brain and cerebrospinal fluid (CSF) concentrations of ubiquitin C-terminal hydrolase-1 (UCH-L1), glial fibrillary acidic protein (GFAP), αII-spectrin breakdown products (SBDP150, SBDP145, and SBDP120), and their relationship to neuropathology in an animal model of kainic acid (KA) excitotoxicity. Triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 75 publications
2
27
0
Order By: Relevance
“…22 Our results indicated that the nanoparticles of nanotube, CB, and C60 caused in vitro neurotoxicity potential by inducing αII-SBDP of SBDP150/145, which have been demonstrated in previous studies as biomarkers for compound-induced neurodegeneration and neurotoxicity in rat. 2325 While SBDP150/145/120 are useful as markers for in vitro evaluation of NP-induced neurotoxicity in our current studies, they are potential biomarkers to assess the NP-induced neurotoxicity in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…22 Our results indicated that the nanoparticles of nanotube, CB, and C60 caused in vitro neurotoxicity potential by inducing αII-SBDP of SBDP150/145, which have been demonstrated in previous studies as biomarkers for compound-induced neurodegeneration and neurotoxicity in rat. 2325 While SBDP150/145/120 are useful as markers for in vitro evaluation of NP-induced neurotoxicity in our current studies, they are potential biomarkers to assess the NP-induced neurotoxicity in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…Increased levels of UCH-L1 in serum or CSF have been documented in several in vivo models of neuronal injuries such as TBI, stroke, hypothermic circulatory arrest and neurotoxicity [15][16][17][18] . Several studies have also shown increased GFAP levels in serum following experimental TBI 19, 20 .…”
Section: Discussionmentioning
confidence: 99%
“…CSF and serum samples were analyzed using GFAP and UCH-L1 Banyan Biomarker's proprietary sandwich ELISA as described in previous publications [9][10][11][12][13] antibody or streptavidin-HRP conjugates catalyzed the reaction with tetramethyl benzidine, and the product was quantitated by absorbance at 450nm using a microplate spectrophotometer (BMG, Optima FluoStar, Germany). Standard curves were generated using recombinant proteins corresponding to measured analyte for each assay and four-parameter non-linear regression analyses were applied to determine analyte quantity using SigmaPlot software (Systat, Chicago, IL).…”
Section: Serum and Csf Biomarker Analysismentioning
confidence: 99%
“…Depending on the stimulus paradigms used to evoke SE in these models, spontaneous seizures can begin within days (Bumanglag and Sloviter, 2008; Norwood et al, 2010). In all of these models, considerable neuronal cell death is observed throughout the brain and astrocytes begin to exhibit signs of reactive gliosis soon after evoking SE (do Nascimento et al, 2012; Glushakova et al, 2012; Lauritzen et al, 2012a). …”
Section: Status Epilepticus Can Results In Temporal Lobe Epilepsymentioning
confidence: 99%